THE COMPOSITION OF CATCHES BELAT DURING THE DAY AND NIGHT IN THE VILLAGE OF BUNGA SIAK REGENCY OF RIAU, INDONESIA - Sutrisno Eko Hadmojo; Pareng Rengi; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was held in the village of Bungaraya, Siak Regency of Riau. The purpose of the study is to find out the composition of catches and the splint during night. The method used is the survey method. The fish consists of four types i.e. rasau, shrimp fish catch pole, fish baung and selais. The results of the analysis of the data on catches during the day and night there are differences the amount of weight or number of individuals where the catch at night more than it is during the day, because the target fish species are nocturnal.Keywords: Belat, rasau, shrimp fish catch pole, baung, selais, nocturnal